Minimum Wage in Readymade Garments Industry in Bangladesh - Hasan, Mohammad Ashraful (American Journal of Trade and Policy, 2019)
Manufacturing Ready-Made Garment (RMG) is labour intensive and low wage based industry. Nowhere, this industry was static or permanent basically on account of wage. As soon as any country became developed, the apparel and textile industry left that country. RMG is highly focused on the relocation of production. The relocation take place from high wage regions to low cost production regions just like water flows down-stream always. This single sector is dominating Bangladesh economy Since ‘80s. In Bangladesh different sectors have different wage levels according to the nature of job. The Minimum Wages Board recommended or re-recommended minimum wages of the 42 industrial sectors. The minimum wage of this very sector is lower than other sectors within the country and among the RMG manufacturing countries as well. On the contrary, within the country, for the same sector – RMG, there are dissimilarity in the minimum wage. Bangladesh Export Processing Zone Authority (BEPZA) declares the same for the industries inside Export Processing Zones (EPZ) which is higher than the declaration by Minimum Wage Board for outside EPZ factories. Minimum wage board has classified the non-EPZ workforces into seven grades according to their skills with seven different wage levels. Contrary, EPZs workers are divided into five categories. BEPZA has fixed higher wages and benefits compere to non-EPZ factories. Moreover, the study finds that the grading system has many loopholes which is not based on well thought and planned. There are so many posts and positions required to run an RMG factory that are not mentioned in the gazette. There is no guideline on how to measure workers’ competency for a particular grade and for how long a worker will be retained in the same grade. These loopholes are helping the employers to manipulate in determining workers’ grade. Minimum wage structure is applicable for whose positions mentioned in the gazette and entitled to all types of benefits mentioned in the law including overtime (OT) payment at double rate of wage. To avoid extra overtime payment factory management promotes or changes the designations like executive, supervisor etc. who are getting comparatively higher wage to keep them away from OT benefits. All those anomalies need to be addressed for properly.